Cultural Dialogue of Russian Regions: Partnership Mechanisms of the Government, Society and Business - Olga V. Shlykova; Ольга Владимировна Шлыкова (Observatory of Culture, 2015)
The article considers some topical issues of interaction between the civil society, government and business on implementation of the Bases and Strategy of state cultural policy. Author pays special attention to the analysis of experts and specialists’ speeches at the Second Cultural Forum of Russian Regions, that took place in Moscow and Yakutsk on September 25, 2015 with the participation of the Council of Civic Chambers of Subjects of the Russian Federation, the Ministry for Development of the Far East of the Russian Federation, the Ministry of Culture of the Russian Federation, the Federal Agency on Affairs of Nationalities, the Government, the Civic Chamber of the Republic of Sakha (Yakutia), leading cultural experts, leaders of education, youth, national, information policy, specialists in social entrepreneurship, representatives of higher education institutions, etc. Рассматриваются актуальные вопросы взаимодействия государства, власти и бизнеса по реализации Основ и Стратегии государственной культурной политики. В центре внимания - анализ выступлений экспертов и специалистов на II Культурном форуме регионов России, который состоялся в Москве и Якутске 25 сентября 2015 г. при участии Совета общественных палат субъектов Российской Федерации, Министерства Российской Федерации по развитию Дальнего Востока, Министерства культуры Российской Федерации, Федерального агентства по делам национальностей, Правительства и Общественной палаты Республики Саха (Якутия), ведущих экспертов в области культуры, руководителей сфер образования, молодежной, национальной, информационной политики, специалистов социального предпринимательства, представителей вузовской общественности и др.